Memahami Makna Nafs, Aql, dan Qalb - Suparta, Suparta (Ta’dibuna: Jurnal Pendidikan Islam, 2018)
There are meanings of nafs (soul): first is nafs sawiyah mullahamah, a soul which emphasizes on the meaning of the potential of man; second, nafs Alammarah which has negative inclination, and third, nafs al-rnuthmainnah; it is a soul which gets bless from Allah swt. ’Aql in the Qur’an denotes an ability of reasoning like thinking (tafakkur), observing (nadzara), interpreting (i’tibar), meditating (tadabbur), reflecting (ta’ammul), deep insight (istibsar), remembering (tadzakkur), etc. Based on several Qur’anic verses, we can find that qalb means an instrument to comprehend reality and values.